2011
DOI: 10.1073/pnas.1101018108
|View full text |Cite
|
Sign up to set email alerts
|

Rural household income and inequality under the Sloping Land Conversion Program in western China

Abstract: As payment for ecosystem services (PES) programs proliferate globally, assessing their impact upon households’ income and livelihood patterns is critical. The Sloping Land Conversion Program (SLCP) is an exceptional PES program, in terms of its ambitious biophysical and socioeconomic objectives, large geographic scale, numbers of people directly affected, and duration of operation. The SLCP has now operated in the poor mountainous areas in China for 10 y and offers a unique opportunity for policy evaluation. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
91
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(98 citation statements)
references
References 16 publications
4
91
1
2
Order By: Relevance
“…Payment for Ecosystem Services (PES) is an effective policy mechanism that can leverage more external resources to sustain and improve ES via the conversion of non-market values of ES into individual economic incentives [29,30]. Over the last decades, PES programs aimed at improving ES and alleviating poverty are becoming important and thus are undergoing rapid development in both developed and developing countries [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Payment for Ecosystem Services (PES) is an effective policy mechanism that can leverage more external resources to sustain and improve ES via the conversion of non-market values of ES into individual economic incentives [29,30]. Over the last decades, PES programs aimed at improving ES and alleviating poverty are becoming important and thus are undergoing rapid development in both developed and developing countries [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Ouyang et al 1999Ouyang et al , 2016Chen and Zhang 2000;He et al 2005) as well as case studies examining the impacts of PES on both livelihoods and environmental outcomes (e.g. Cao et al 2010;Li et al 2011;Liu et al 2008;Yang et al 2013aYang et al , 2013b; see also Suich et al 2015). However, to our knowledge, ours is the first analysis to examine the spatial covariation of poverty and ES at the scale of China.…”
Section: Introductionmentioning
confidence: 86%
“…Research results of similar ecological restoration projects, such as Sloping Land Conversion Program (SLCP), showed that the SLCP's direct impact on the income of participant households was insignificant. Instead, the increase of household income can be mainly attributed to the significant acceleration of the non-agricultural labour force (Li et al, 2011;Yin et al, 2014;Lin and Yao, 2014). Likewise, rocky desertification control has reduced the demand for agricultural labour and has promoted the transfer of agricultural surplus labour to non-agricultural employment (Xiao et al, 2012), which may have indirectly contributed to an increase of household income.…”
Section: The Challenges That Are Confronted With In Rocky Desertificamentioning
confidence: 99%